Old lesbians: Gendered histories and persistent challenges. (October 2015) - Waite, Helen
Abstract : Aim: This article provides an overview of how gender and historical contexts influence the well‐being of old lesbians. It aims to inform the practice of aged care providers in addressing the needs of these women. Methods: The lived experience of old lesbians is examined using feminist methodology with a focus on hegemonic femininity, social structures and cultural life. Results: Old lesbians being selectively 'open', their use of health services and desire for lesbian‐specific aged care are all influenced by lesbophobia, a complex of discriminations. The age women began living as lesbian and fluidity of orientation, are central to understanding their particular needs. Many old lesbians have created social groups and intentional communities where there is support and freedom. Conclusion: The current 'inclusivity' approach is insufficient for culturally appropriate aged care for old lesbians. Developing practices that meet their needs requires better understanding of lesbians' different life courses and why they created lesbian cultures.